Solutrean Chronology & Lithic Variability in Vasco-Cantabrian Spain - Lawrence Guy STRAUS; F. BERNALDO DE QUIRÓS; Victoria CABRERA VALDÉS; G. A. CLARK (Zephyrus, 2009)
RESUMEN: Recientes excavaciones en la zona cantábrica suministran datos que apuntan a una variabilidad en las industrias del Solutrense. Basado en pruebas de radiocarbono parece evidenciarse una contemporaneidad entre el fenómeno solutrense de la España Cantábrica y el Rhone Valley. La industria de puntas diagnostican un resultado de un proceso tecnológico convergente. ABSTRACT: Recent excavations in Cantabrian cave deposits provide evidence of Solutrean industrial variability and provocative chronological information. On the basis of radiocarbon there is strong evidence for contemporeanity between the Solutrean phenomena of Cantabrian Spain and in the Rhone Valley. The stone-points diagnostic would probably be the result of convergent technology. There is considerable evidence for variability among artifacts assemblages (shown in their respective coefficients of variation). It is therefore difficult to characterize Cantabrian collections from the time range in question in a general way. It seems more fruitful to try and demonstrate the existence of functional parameters for observed artifact variability.